Community football teams for people with intellectual disabilities in secure settings: "They take you off the ward, it was like a nice day, and then you get like medals at the end". Issue 2 (15th May 2017) - Hudson, Nicholas Andrew; Mrozik, Jennifer Hella; White, Rose; Northend, Kristian; Moore, Steve; Lister, Katherine; Rayner, Kelly
Abstract : Background: People with learning disabilities (LD) are particularly vulnerable to mental health and behavioural difficulties, and it has been shown that regular exercise can improve psychosocial well‐being as well as physical fitness. This research aims to explore the experiences of men with LD detained in secure settings who have engaged in community football training programmes and identify the benefits of such provision. Method: Interviews were conducted with eight patients in a forensic LD service, discussing their experiences of participating in community football. Template analysis was undertaken on the transcripts. Results: Two master themes were identified: physical fitness and psychosocial benefits. As the analysis progressed, new emerging themes were identified around role identity and achievement, as well as extending and refining some of the themes from the original template including fun and belonging. Some anticipated themes were removed from the template entirely. Conclusion: The psychosocial benefits of organised community sports programmes far outweigh the physical health benefits. Careful consideration must be given to where on a treatment and rehabilitation pathway non‐traditional therapeutic interventions such as sports programmes are offered as an adjunct to specific risk reduction interventions for people with LD in secure settings.